Implementation of Quran Learning Using At-Tartil Method in Islamic Elementary School Wahid Hasyim Sekardangan - Darmansyah Darmansyah; Nur Maslikhatun Nisak (Universitas Muhammadiyah Enrekang, 2023)
The At-tartil method familiarizes students with reading the al-quran directly (without spelling) by including/practicing reading tartil according to ulumul tajwid and ulumul ghorib rules. A qualitative approach was used in this study to determine a research process that produces descriptive data in the form of written or spoken words from people and observable behavior and an approach that describes the reality of an event in detail, depth, and comprehensively. From the Results of observation and interviews conducted by the wahid hasyim elementary school Sidoarjo, it can be concluded that learning the al-quran using the at-tartil method, which students follow, requires careful and planned preparation before starting the learning process. As to learning the al-quran in the at-tartil way in elementary school, Wahid Hasyim Sekardangan Sidoarjo to improve students’ al-uran reading skills in reading tartil according to the rules ulumul tajwid and ulumul ghorib in elementary school Wahid Hasyim Sekardangan Sidoarjo. Because based on the results of interviews and observations of the author, around 85% of the students could understand and master the learning material on the method at-tartil in the al-Quran in class. Thus, a conclusion can be drawn that the level of success in learning the al-quran using the At-Tartil method is excellent and optimal for Implementation by the wahid hasyim elementary school Sidoarjo.